2008
DOI: 10.1002/pits.20311
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to participation in kindergarten literacy instruction for a student with augmentative and alternative communication needs

Abstract: Preliminary findings and implications from this study were presented at the 45th Annual Convention of the International Reading Association in Indianapolis, Indiana, April 30, 2000.The author would like to express sincere gratitude to the kindergarten teacher who cooperated with this study and willingly allowed the researcher unlimited access to her classroom. The author also thanks all the school personnel and students who made this study possible as well as the Purdue University AAC Group for their feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Additional research is needed to examine salient barriers to students' use of their AAC devices in general education classrooms, which may include limited availability, student competence in using the device, expectations and training of support personnel, occurrence of comprehensive planning, peer attitudes, or provision of communication opportunities (Beck, 2009;Calculator, 2009;Pufpaff, 2008;Stoner, Angell, & Bailey, 2010). Educators may also draw on the Participation Model (Beukelman & Mirenda, 2005) to evaluate the access and opportunity associated with students' AAC devices in inclusive settings.…”
Section: Discussionmentioning
confidence: 97%
“…Additional research is needed to examine salient barriers to students' use of their AAC devices in general education classrooms, which may include limited availability, student competence in using the device, expectations and training of support personnel, occurrence of comprehensive planning, peer attitudes, or provision of communication opportunities (Beck, 2009;Calculator, 2009;Pufpaff, 2008;Stoner, Angell, & Bailey, 2010). Educators may also draw on the Participation Model (Beukelman & Mirenda, 2005) to evaluate the access and opportunity associated with students' AAC devices in inclusive settings.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the use of high-tech, speech-generating augmentative and alternative communication devices in writing makes it possible for students with SSPI to express their thoughts (Lidström, 2011); such use thus contributes significantly to literacy development (Wilkins & Ratajzcak, 2009). Furthermore, because there often exists a huge gap between a child's language-reception and language-expression abilities, high quality reading and writing instruction is needed to bridge this gap (Pufpaff, 2008) and thereby prevent an arrest in literacy development (Dahlgren Sandberg, 2006).…”
Section: Earlier Researchmentioning
confidence: 99%
“…Several studies have revealed that only a small proportion of classroom time is dedicated to literacy activities for this group of students. One reason seems to be a lack of confidence in supporting literacy learning for these students among educators, speech and language therapists, and parents (Dahlgren Sandberg, 1998;Fallon & Katz, 2008;Larsson, 2008;Light & McNaughton, 1993;Malmqvist, 2001;Pufpaff, 2008;Ruppar, Dymond, & Gaffney, 2011;Zascavage & Keefe, 2007). Such research findings indicate an underestimation of these students' learning potential, which may lead to deprivation of students' capabilities (Sen, 1992) and which has been associated with discrimination by Zascavage and Keefe (2004, p. 231):…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity and access barriers that have limited reading development arise from professional and societal attitudes, educational practice, instructional priority, lack of knowledge, and a paucity of research-based instructional methods [14,15]. First, the belief that literacy skill limitations are "innate" [16] has influenced the instructional curriculum of students with significant ID.…”
Section: Factors Influencing Reading Developmentmentioning
confidence: 99%